2008
DOI: 10.1136/bmj.a2509
|View full text |Cite
|
Sign up to set email alerts
|

Exercise on prescription for women aged 40-74 recruited through primary care: two year randomised controlled trial

Abstract: Objective To assess the effectiveness of a primary care based programme of exercise on prescription among relatively inactive women over a two year period.Design Randomised controlled trial.Setting 17 primary care practices in Wellington, New ZealandParticipants 1089 women aged 40-74 not undertaking 30 minutes of moderate intensity physical activity on at least five days of the weekIntervention Brief physical activity intervention led by nurse with six month follow-up visit and monthly telephone support over n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
188
1
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(205 citation statements)
references
References 25 publications
8
188
1
8
Order By: Relevance
“…Two studies found an inverse association between PA and any domain of QoL. 8,27 Most studies examined the association between PA and overall QoL score. But as the instruments used were different, different domains of QoL were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies found an inverse association between PA and any domain of QoL. 8,27 Most studies examined the association between PA and overall QoL score. But as the instruments used were different, different domains of QoL were included.…”
Section: Resultsmentioning
confidence: 99%
“…To be continued Lawton et al 27 Individuals were divided into control and intervention groups. Both were assessed at the baseline, at 12 months and 24 months.…”
mentioning
confidence: 99%
“…In contrast, some studies revealed an increase in falls and injuries among an intervention group which was encouraged to become more physically active 22,23 . Therefore, clinical studies with a multifactorial approach that investigate the characteristics of fallers with different levels of physical activity could offer some insight for rehabilitation and preventive interventions in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, reporting of the content of interventions adopting MI is often brief and lacking in specific detail making it difficult to replicate or pinpoint the precise techniques that may be affecting behavior change. Many MI studies lack detail in their descriptions of the precise techniques adopted, how they were delivered, practitioner training and competency in MI (Douaihy, Kelly, & Gold, 2014) and some do not provide any detailed description of the MI intervention components at all (e.g., Ackerman, Falsetti, Lewis, Hawkins, & Heinschel, 2011;Armit et al, 2009;Harland et al, 1999;Kerse, Elley, Robinson, & Arroll, 2005;Lawton et al, 2008;Penn et al, 2009;Whittemore et al, 2009). …”
Section: The Need For Better Reporting Of MI Techniquesmentioning
confidence: 99%